Can Strong Financials Prevent Collapse? Insights from the Consumer Goods Sector (2017–2022) - Hasanah, Sevia; Rahman, Arief; Mahsina, Mahsina (Universitas Bhayangkara Surabaya, 2025)
This study aims to analyze how profitability ratio, liquidity ratio, activity ratio, leverage ratio, and sales growth impact financial distress in the goods and consumer goods industry from 2017 to 2022. In this study, saturated sampling is used for the sampling technique. The classical assumption test is used for data analysis. In this study, profitability ratio (X1), liquidity ratio (X2), activity ratio (X3), leverage ratio (X4), and sales growth (X5) are independent variables, and financial distress (Y) is the dependent variable. The results of this study indicate that the profitability ratio measured using return on assets (ROA) has a positive effect on financial distress, the liquidity ratio measured using the current ratio (CR) does not affect financial distress, the activity ratio measured using total asset turnover (TATO) has a negative effect on financial distress, the leverage ratio measured using the debt to asset ratio (DAR) has a positive effect on financial distress, and sales growth has no effect on financial distress.